2009
DOI: 10.1021/jp901724d
|View full text |Cite
|
Sign up to set email alerts
|

Role of Quantum Coherence and Environmental Fluctuations in Chromophoric Energy Transport

Abstract: The role of quantum coherence and the environment in the dynamics of excitation energy transfer is not fully understood. In this work, we introduce the concept of dynamical contributions of various physical processes to the energy transfer efficiency. We develop two complementary approaches, based on a Green's function method and energy transfer susceptibilities, and quantify the importance of the Hamiltonian evolution, phonon-induced decoherence, and spatial relaxation pathways. We investigate the Fenna-Matth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
394
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(408 citation statements)
references
References 33 publications
(108 reference statements)
12
394
2
Order By: Relevance
“…In a separate study [66], the nonMarkovian processes were seen to be prominent in the reorganization energy regime, also noted by Silbey and coworkers [67] who showed that the reorganization energy and the bath relaxation rate played critical roles during the energy transfer process. Chen et.…”
Section: Zeno Effect At Dissipative Sinks In the Photosynthetic supporting
confidence: 62%
“…In a separate study [66], the nonMarkovian processes were seen to be prominent in the reorganization energy regime, also noted by Silbey and coworkers [67] who showed that the reorganization energy and the bath relaxation rate played critical roles during the energy transfer process. Chen et.…”
Section: Zeno Effect At Dissipative Sinks In the Photosynthetic supporting
confidence: 62%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] Ideas such as noise-assisted transport, 9,10,[12][13][14]16 quantum locking, and momentum rejuvenation 14 have been used to suggest how interactions with the environment can help speed up energy transport in networks of chromophores. a) n.linden@bristol.ac.uk b) fred.manby@bristol.ac.uk However, it is still not certain whether these phenomena play a role in the real biological context, where the assumptions inherent in the master-equation approach may not apply.…”
Section: Introductionmentioning
confidence: 99%
“…20 Furthermore, extensive work has been carried out to investigate the efficiency and robustness of the FennaMatthews-Olson (FMO) PPC with respect to fluctuations in the protein environment, with findings showing that thermal fluctuations can enhance EET via so-called environmentassisted quantum transport (ENAQT). [21][22][23][24][25][26] Similar studies of photosynthetic systems have investigated EET efficiency optimisation with respect to environmental model parameters such as temperature or exciton trapping rates. 6,20,21,27,28 The effect of removing a chromophore on EET efficiency has also been investigated, and it has been suggested that photosynthetic EET networks display a robustness to the loss of a chromophore in the network through the utilisation of multiple EET pathways.…”
Section: Introductionmentioning
confidence: 99%